The Impact of Foreign Remittances on Economic Growth: Evidence from Zimbabwe - Maune, Alexander; Matanda, Ephraim (Acta Universitatis Danubius. Œconomica, 2022)
This article examined the impact of foreign remittances on economic growth in Zimbabwe. Secondary data collected from the World Bank`s World Development Indicators database was employed to empirically examine the nature of the relationship between the two variables, for the period 1960-2020. The autoregressive distributed lag model was used. The major findings reveal both unidirectional and bi-directional causality linkages between foreign remittances and economic growth during the three periods under review. Foreign remittances showed a positive and significant influence on the gross domestic product in Zimbabwe. The period before dollarization gave a strong negative influence on Zimbabwe’s economic growth. The dollarization period showed a strong positive correlation between the two variables under study in Zimbabwe. The error correction gave a very strong negative statistical relationship with the rate of economic growth in Zimbabwe. This article has practical implications, especially for policy formulation and implementation at individual and government levels. The article closed the gap in knowledge by drawing attention to the nature of the relationship between foreign remittances and economic growth in Zimbabwe during the three different economic cycles examined.